Europium oxide on carbon nitride for electrocatalytic glycerol oxidation coupled with hydrogen evolution reaction - Jana, Jayasmita; Sharma, Tata Sanjay Kanna; Ghanem, Mohamed A.; Choi, Won Mook; Gopinath, Chinnakonda S.; Hur, Seung Hyun (Separation and Purification Technology, 2025)
{The integration of the electrochemical glycerol oxidation reaction (GOR) with the hydrogen evolution reaction (HER) has emerged as a promising alternative to the sluggish oxygen evolution reaction (OER) in water splitting toward the development of renewable and clean energy sources. However, suitable electrodes that facilitate redox kinetics while increasing the selectivity of the desired product(s) are still required. Herein, a series of europium oxide (Eu2O3) anchored on graphitic carbon nitride (g-CN) nanoaggregates (g-CNEux
Keywords: carbon support; electrocatalysis; Glycerol; HER; Rare earth metal

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen